(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3MQa GdbGa , hjTJed Ydi MQa JSYI cJH s
(3BNQgG (B:s
(3ef cJGH GdfLhe bhdg (B: (3hGdSGMQ cGaQ aLYd GdefLe GdPi jJYde GdfLhe ddMce HgG hYdjgG hjfSH GdJCKjQGJ ef GdSYGOI hGdTbGhI EdjgG cGaQkG , hfYhP HGdgd ef Pdc hfSCdg GdYUeI ai Gdbhd hGdYed s
(3GdLRA GdSGOS ef fSNI CNQis
(3HMhGTjgG JYdjbGJs
(3hcJHJ GdYfhGfGJ HGdMeQIs
(3GdfSNI HgG MhGT s
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs